GRANTING PRIVILEGES TO PRISONERS IN THE PENOLOGICAL PRACTICE OF THE REPUBLIC OF MACEDONIA - Gruevska Drakulevski, Aleksandra (Iustinianus Primus Law Review, 2013)
The author of the paper addresses a very important institute in the process of re-socialization of prisoners - the granting of privileges to prisoners. Privileges of prisoners are incentives that motivate prisoners to actively engage in their own rehabilitation. The basic function of privileges is to stimulate inmates to a disciplinary and responsible behavior, and exemplary efforts in work and other rehabilitative activities during the serving of their sentence. In this article the author specifically focuses on international standards and regulations in the Republic of Macedonia concerning the conditions and procedure for granting privileges to prisoners. In a separate chapter the author analyzes a number of granted privileges to prisoners in the Republic of Macedonia in the period between 2008 and 2012, and their subsequent abuse. The author concludes that our penological practice regarding privileges of prisoners has a positive attitude, because it is a very suitable method for dealing with inmates. When deciding to grant privileges to prisoners the prescribed criteria for granting should be respected. Also, prisoners should clearly acknowledge that their active involvement in the process of their own re-socialization will pay off; they will be granted privileges because of their positive behavior. On the other hand, selective granting of privileges to prisoners can have the opposite effect.
Keywords: privileges, re-socialization, rehabilitation, prisoners